2002
DOI: 10.1144/petgeo.8.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic water injection: improved oil recovery at zero cost

Abstract: Cyclic injection is a process that improves waterflooding efficiency in heterogeneous reservoirs. The concept of cyclic injection is based on (1) pulsed injection and (2) alternating waterflood patterns. Cyclic injection has been successfully applied in a number of sandstone and carbonate oil fields in Russia. In the rest of the world, pulsed injection has had limited application, and only in naturally fractured reservoirs. Although changing the waterflood patterns is a common approach to deal with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…Such injection rate with pulsed injection and alternating flow directions would result in noticeable differences in sweep efficiency and oil recovery in field scale and lab experiments, as well as in flow dynamics and mass transfer in miscible displacements, depending on the actual situations. There are many different types of time‐dependent displacement rates u ( t ), either in a sinusoidal or step‐size manner, or with hammer pulsing or bang–bang types . However, to easily identify the effect of different displacing stages, we adopt the step‐size injection/extraction rates as that in previous studies .…”
Section: Time‐dependent Displacement Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Such injection rate with pulsed injection and alternating flow directions would result in noticeable differences in sweep efficiency and oil recovery in field scale and lab experiments, as well as in flow dynamics and mass transfer in miscible displacements, depending on the actual situations. There are many different types of time‐dependent displacement rates u ( t ), either in a sinusoidal or step‐size manner, or with hammer pulsing or bang–bang types . However, to easily identify the effect of different displacing stages, we adopt the step‐size injection/extraction rates as that in previous studies .…”
Section: Time‐dependent Displacement Ratementioning
confidence: 99%
“…Moreover, a series of lab experiments with temporal variation of injection rate in vapor extraction (VAPEX) process showed that the oil recovery was improved by 19–60%, depending on the permeability of model . Other successful applications of the time‐dependent fluid injection rate were also reported . However, in other studies, the oil recovery with time‐dependent displacement rate is not apparently improved or even lower than that of constant injection rate .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the injection rates are formulated in dimensionless form as expressed by Equations (16)(17)(18)(19)(20):…”
Section: Physical Problem and Governing Equationsmentioning
confidence: 99%
“…[19] From the experiments, high oil recovery rates were reported for injections characterized by shorter periods and large amplitudes. In particular, Surguchev et al used cyclic injection with water to enhance oil production.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, in a fractured reservoir ( Fig. 1(b)), direct application of hydraulic wave sources to a fracture can induce a periodic pressure gradient between a fracture and the surrounding rock matrix, such that transport of the bypassed oil from the rock matrix into the fracture space can be enhanced (Groenenboom et al (2003); Jeong et al (2011); Owens and Archer (1966); Stirpe et al (2004); Surguchev et al (2002)). On the other hand, it has been suggested that the seismic waves increase permeability within hydrocarbon formations.…”
Section: Introductionmentioning
confidence: 99%